Spatial Deixis in Moroccan Tachelhit Variety - Boussaid, Youness (International Journal of Language and Literary Studies, 2022)
This paper investigates spatial deixis in Moroccan Tachelhit Variety. Deixis is a word of Greek origin which means ‘pointing.’ The paper explores the means that Tachelhit offers its speakers for spatial deictic reference, an important pragmatic aspect that linguists of Tachelhit have not heeded to. Tachelhit has a rich spatial deictic system which is thus categorized into: Demonstratives, Adverbs of Place, Prepositions, Motion Verbs, and Presentatives. Tachelhit has a four-term spatial deictic system which changes according to the interplay of gender, proximity, distance, and absence. The paper also discovers that Tachelhit is a language that benefits from spatial deictic iconicity. The two major data collection methods that were used in this qualitative paper are content analysis and elicitation technique. Some examples from other languages (English, Latin, Turkish, Indonesian, Bantu, and French) are provided for cross-linguistic comparison and instantiation.